Prototype Pengontrolan Pintu Pagar Otomatis Berbasis Android - Liza Safitri; Pordi Sahidit (Jurnal Bangkit Indonesia, 2019)
Fence is one of the basic needs in human life, a home must provide a sense of security for its owner. To achieve the above objectives, the authors make Prototype Controlling Automatic Android Turnstile. The system will also be equipped with an Android-based application to open and close the gate as a helper to the homeowner. The results of this study indicate that the application is functioning properly and can be used.In this study, the drive media, Application Servo motor and Bluetooth HC Module 05, which can be connected to the Android Bluetooth with the farthest distance of 5.5 m.The results of this research are testing the prototype and each component function, android-based smart home automatic smart system is obtained which only moves and opens the human gate. This prototype was made with tools such as Arduino IDE, Fritzing and MIT App Inventor.